Political and Social Viewpoints of High School Students: How do Social Media Influencers, Cancel Culture, and Political Correctness affect these? - Ortega, Zamir Adriel; Puerto, Richelle Louveine; Fernandez, Ghenard; Mabalay, Leahkim Asseren; Sugay, Quelvin Renzo; Villarama, Joseph (Journal of Interdisciplinary Perspectives, 2024)
Social media usage, especially among young people, has become intertwined with daily life. High school students, who are heavily exposed to social media, are influenced by influencers, cancel culture, and political correctness. This study explored how these factors affect students’ perspectives on political and social issues. A purposive sampling technique was used to amass 12 participants. Data gathering used the administration of semi-structured interviews, recording audio, and obtaining written responses. Thematic analysis was used in analyzing the transcription of the recordings from the interview. The findings revealed that political correctness significantly influences students’ viewpoints, while influencers and cancel culture have a lesser impact. Participants emphasized the importance of research, personal growth, and maturity over cancel culture and influencers. Further research is needed, involving older participants and diverse settings, due to limited literature on this topic.